Limnohabitans planktonicus sp. nov. and Limnohabitans parvus sp. nov., planktonic betaproteobacteria isolated from a freshwater reservoir, and emended description of the genus Limnohabitans - Kasalický, Vojtěch; Jezbera, Jan; Šimek, Karel; Hahn, Martin W (International journal of systematic and evolutionary microbiology, 2010)
Two bacterial strains, II-B4(T) and II-D5(T), isolated from the meso-eutrophic freshwater Římov reservoir (Czech Republic), were characterized phenotypically, phylogenetically and chemotaxonomically. Both strains were chemo-organotrophic, facultatively anaerobic, non-motile rods, with identical DNA G+C contents of 59.9 mol%. Their major polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine and their major fatty acids were C(16 : 1)ω7c/C(16 : 1)ω6c, C(16 : 0), C(18 : 1)ω7c/C(18 : 1)ω6c and C(12 : 0). Both strains contained Q-8 as the only respiratory quinone component. The 16S rRNA gene sequences of the two strains possessed 99.1 % similarity; however, the level of DNA-DNA reassociation was only 26.7 %. The strains can also be discriminated from each other by several chemotaxonomic and biochemical traits. Phylogenetic analysis of the 16S rRNA gene sequences revealed the affiliation of both strains with the genus Limnohabitans within the family Comamonadaceae. The two investigated strains represent the first isolated members of a narrow phylogenetic cluster (the so-called R-BT065 cluster) formed by a large number of environmental sequences and abundant populations detected in the pelagic zones of various freshwater habitats. We propose to place the two strains in separate novel species within the genus Limnohabitans, Limnohabitans planktonicus sp. nov., with the type strain II-D5(T) (=DSM 21594(T) =CIP 109844(T)), and Limnohabitans parvus sp. nov., with the type strain II-B4(T) (=DSM 21592(T) =CIP 109845(T)). The description of the genus Limnohabitans is emended accordingly.
Keywords: DNA bakterií; Phylogeny; Comamonadaceae; techniky typizace bakterií; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; zastoupení bazí; RNA ribozomální 16S; Phenotype; Base Composition; RNA, Ribosomal, 16S; sladká voda; sekvenční analýza DNA; DNA, Bacterial; mastné kyseliny; Fresh Water; Phospholipids; fylogeneze; fenotyp; Czech Republic; Ubiquinone; Bacterial Typing Techniques; fosfolipidy; Česká republika; ubichinon; Fatty Acids